Epidemiological evidence that indoor air pollution from cooking with solid fuels accelerates skin aging in Chinese women. Issue 2 (August 2015) - Li, Miaozhu; Vierkötter, Andrea; Schikowski, Tamara; Hüls, Anke; Ding, Anan; Matsui, Mary S.; Deng, Binwei; Ma, Chuan; Ren, Aiguo; Zhang, Juan; Tan, Jingze; Yang, Yajun; et al.
Highlights: Indoor air pollution is a major public health challenge in China. Cooking with solid fuels is one main source of indoor air pollution in China. Cooking with solid fuels accelerates wrinkle rates in Chinese women. Corroborates known association between outdoor air pollution and skin aging. Indoor air pollution might be a further risk factor for skin aging. Abstract: Background : Recently, we showed that outdoor air pollution exposure from traffic and industry is associated with an increased risk of skin aging in Caucasian women. In China, indoor air pollution exposure caused by the use of solid fuels like coal is a major health problem and might also increase the risk of skin aging in Chinese women. Objective : As cooking with solid fuels is a major source of indoor air pollution exposure in China, we aimed to test if cooking with solid fuels is associated with more pronounced skin aging in Chinese women. Methods : We conducted two cross-sectional studies in China to assess the association between cooking with solid fuels and signs of skin aging. In Pingding (in northern China) we assessed N  = 405 and in Taizhou (in southern China) N  = 857 women between 30 and 90 years of age. Skin aging was evaluated by the SCINEXA™ score. Indoor air pollution exposure, sun exposure, smoking and other confounders were assessed by questionnaires. Associations were then tested by linear and logistic regression analyses adjusted for further confounders. Results : The analysis showed that cooking with solid fuels was significantly associated with a 5–8% more severe wrinkle appearance on face and an 74% increased risk of having fine wrinkles on back of hands in both studies combined, independent of age and other influences on skin aging. Conclusion : The present studies thus corroborate our previous finding that air pollution is associated with skin aging and extend it by showing that indoor air pollution might be another risk factor for skin aging.